Emerging capital markes in financial globalization - Balázs Pálosi-Németh (Transformation, Integration and Globalization Economic Research (TIGER), 2007)
It must be admitted that in modern economies, financial systems play an important role in allocating scarce resources, helping channel individual or household savings to the corporate sector, and allocate funds among companies. The two main pillars of the financial system are the banking system and the capital markets. In this paper I investigate whether capital markets can fulfil its essential functions in the transition economies. In the last 3 years a dramatic change could be witnessed in the performance of emerging capital markets. While developed stock markets also had excellent years with 15-20% rise annually, emerging and transition markets increased over 50% a year in 2004 and 2005 (Figure 1, page 6). But does their performance reflect real efficiency? Is it a real development or only an illusion? The main objective of the study is to evaluate if the capital markets of new EU member states have the capacity of efficient fund allocation. Well functioning financial intermediation plays a major role in the discussion, enhancing more efficient fund allocation and ultimately higher economic growth. Although it is clarified in related literature that a hybrid (parallel significance of banks and capital market) financial system is favorable to economic growth, this study presents why the stock markets in the post communist member states have limited contribution to this development. Despite that economic policy has boosted stock market orientation in the last 15 years, the evolution of the economies developed to its own direction. The reasons of it are twofold. On the one hand financial globalization spurs the biggest and most liquid companies of our region to cross-border issue, moving to a financial centre and leaving the local stock markets. On the other hand cultural aspects of the households also hinders the emergence of local stock market in Central-Eastern Europe (CEE). In the first main section the related literature is surveyed, cherry picking some particularly important features. This is followed by an analysis of the demand of the different sectors in the economy, namely the: government, corporate and household sectors, for financial markets. Chapter 5 presents case studies concerning possible expedient strategies of the examined markets. The last main section provides the empirical evidences of the hypothesis, followed by possible ways of applicability, policy recommendations and conclusions.
Keywords: 330; Aktienmarkt; Effizienzmarkthypothese; Allokationseffizienz; Schwellenländer; Kapitalmobilität; EU-Mitgliedschaft